Preparation, characterization, and thermal stability of B2O3-SiO2 - Winda Fitriana; Aldes Lesbani (Science and Technology Indonesia, 2017)
Preparation of B2O3-SiO2 compound by inorganic synthesis was carried out. B2O3-SiO2 was characterized by FT-IR spectro-photometer, analysis of crystallinity by XRD, and test of acidity. B2O3-SiO2 was also tested by thermal stability with temperature range at 300-700 ⁰C. The results showed that the FT-IR spectrum of B2O3-SiO2 has some vibrations of B-O, Si-O-Si, Si-O-B stretching, and Si-O-B bending at 1442.8 cm-1, 779.2 cm-1, 925.8 cm-1, and 648.1 cm-1. The X-Ray diffraction pattern results showed that the analysis of B2O3-SiO2 has high crystallinity with two peaks diffraction identified at 26.6⁰ and 20.9⁰. The thermal stability test of B2O3-SiO2 showed that B2O3-SiO2 has high thermal stability with temperature range at 300-700 ⁰C. The results showed that the acidity analysis of B2O3-SiO2 has potential number 122.71 mV so that indicated B2O3-SiO2 was high acidity. Keywords : boric oxide, silica dioxide, boric silica, B2O3-SiO2